Analisis Framing Berita Meninggalnya Mantan Presiden Soeharto di Majalah Tempo dan Gatra - Nur Indah Yogadiasti; Muzayin Nazaruddin (Program Studi Ilmu Komunikasi, 2008)
News about sick until death of the former President Soeharto, covered by various media printed and also electronic. It becomes main report and special feature in various magazine also, such as Gatra and Tempo. There are three considerations in determining Gatra and Tempo as source of study. First, both of them are national weekly news magazine. It means, those magazines cover public widely, so can influence the reader. Second, those magazine have big attention to the death of Soeharto. This is proved from special edition about Soeharto printed by Tempo. While Gatra printed the news of Soeharto till 15 pages. Third, pro and contra about Soeharto which can be seen in Gatra and Tempo. Analytical method applied in this research is Framing Analysis with Zongdang Pan and Gerald M. Kosicki models. In this research, researcher found that Gatra and Tempo is very different in the way reporting the death of Soeharto. By Frame Analysis, we can see how both of magazine frame the news concerning of Soeharto. And it is clear that Gatra tend to look for safe in reporting Soeharto, while Tempo is braver and more artically inpassing opinions.